ANALYSIS OF NURSE'S JOB SATISFACTION BASED ON INTERNAL SERVICE QUALITY MEASUREMENT - Agus Aan Adriansyah; Budhi Setianto; Wiwik Afridah; Akas Yekti Pulih Asih; Stefanus Supriyanto; Venia Ilma Dwi Prastika; Amanatul Istifaiyah (Poltekkes Kemenkes Semarang, 2020)
Nurses who are considered by the hospital to be able to provide maximum health services to patients so that they can increase patient satisfaction. This research was conducted to analyze the job satisfaction of nurses based on Internal Service Quality in the inpatient installation of RSI A. Yani Surabaya. The study was conducted with an observational analytic design and cross-sectional approach. The study population was the nurses in the inpatient installation of RSI A. Yani Surabaya, a total of 104 nurses. The sample size was 78 nurses who were spread in each inpatient room of RSI A. Yani Surabaya. The method of sampling using simple random sampling. Data analysis was performed using binary logistic regression test. The results showed that 98.7% of nurses rated internal service quality as good and 64.1% of nurses said they were satisfied. Based on the statistical test, it was found that the value of p = 0.999 (more than 0.05), which means that internal service quality has no significant effect on job satisfaction of nurses. However, based on the aspect of internal service quality, the aspects of tools and reward and recognition can provide an almost significant effect on job satisfaction of nurses. Provision of tools has 9.23 times less risk of dissatisfying nurses than providing good tools. Likewise, giving rewards and recognition that was less likely to have a 3.34 times risk of making nurses dissatisfied compared to giving good recognition.